Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Number: 4
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

La citoyenneté multiculturelle: une théorie libérale du droit des minorités - Kymlicka, Will (Éditions La Découverte ; Éditions du Boréal, 2001)
Les sociétés contemporaines deviennent de plus en plus des sociétés multiculturelles dans lesquelles les groupes minoritaires ethniques ou nationaux réclament une reconnaissance publique et les moyens de préserver leur identité culturelle. Une revendication qui n'est pas sans susciter des conflits qui menacent parfois l'unité territoriale des États. Pour Will Kymlicka, la réponse à cet enjeu devenu incontournable constitue aujourd'hui l'un des plus grands défis pour la démocratie. Son propos, dans ce livre devenu un classique de la théorie politique, est de défendre une nouvelle conception du statut et des droits des minorités culturelles.
Section: 357 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; citoyenneté; cours; discipline; discours dominant; europe; histoire et politique; inégalités; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis